Metode Diskusi sebagai Strategi Pembelajaran untuk Meningkatkan Prestasi Belajar Siswa pada Mata Pelajaran PAI di SMP Riyadhlul Mubtadiin Mandalawangi Pandeglang - Heri Setiaji; A Zaenal Arifin; Suhaebi; Irfan Anshori (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2026)
This study aims to analyze the implementation of the discussion method in improving the learning achievement of Islamic Religious Education (PAI) at Riyadhlul Mubtadiin Junior High School and examine its theoretical contribution in the development of participatory-based learning strategies. The research uses a qualitative approach with a descriptive type. Data was obtained through observation, interviews, and documentation, then analyzed through data reduction, data presentation, and systematic conclusion drawn. The results of the study show that the application of the discussion method is able to improve students' conceptual understanding, active participation, and critical thinking skills in PAI learning. Theoretically, these findings reinforce the constructivist and humanistic learning paradigm that places students as active subjects in building knowledge through social interaction. The discussion method not only has an impact on the cognitive aspect, but also the affective and social aspects, thus contributing to the formation of religious character and tolerant attitudes. In the normative perspective of Islam, the method of discussion is in harmony with the principle of deliberation as taught in the Qur'an (QS. Ash-Shura: 38), which emphasizes the importance of dialogue and exchange of opinions in the decision-making process. Thus, this study confirms that the method of discussion is not only pedagogically relevant, but also has theological legitimacy in the Islamic educational tradition. This study has implications for strengthening the PAI learning model that is dialogical, reflective, and oriented towards the development of students' holistic competencies.